Biosynthetic Pathways of Brassinolide in Arabidopsis - Noguchi, Takahiro (American Society of Plant Physiologists, 2000)
Our previous studies on the endogenous brassinosteroids (BRs) in Arabidopsis have provided suggestive evidence for the operation of the early C6-oxidation and the late C6-oxidation pathways, leading to brassinolide (BL) in Arabidopsis. However, to date the in vivo operation of these pathways has not been fully confirmed in this species. This paper describes metabolic studies using deuterium-labeled BRs in wild-type and BR-insensitive mutant (bri1) seedlings to establish the intermediates of the biosynthetic pathway of BL in Arabidopsis. The first evidence for the conversion of campestanol to 6-deoxocathasterone and the conversion of 6-deoxocathasterone to 6-deoxoteasterone is provided. The later biosynthetic steps (6-deoxoteasterone → 3-dehydro-6-deoxoteasterone → 6-deoxotyphasterol → 6-deoxocastasterone → 6α-hydroxycastasterone → castasterone → BL) were demonstrated by stepwise metabolic experiments. Therefore, these studies complete the documentation of the late C6-oxidation pathway. The biosynthetic sequence involved in the early C6-oxidation pathway (teasterone → 3-dehydroteasterone → typhasterol → castasterone → BL) was also demonstrated. These results show that both the early and late C6-oxidation pathways are functional in Arabidopsis. In addition we report two new observations: the presence of a new branch in the pathway, C6 oxidation of 6-deoxotyphasterol to typhasterol, and increased metabolic flow in BR-insensitive mutants.